Transparent, Complex, Sustainable Challenges for Contemporary Facade Engineering - L. Blandini (Challenging Glass Conference, 2018)
The tasks a façade has to fulfill in contemporary high-end architecture have become more and more complex and challenging. An innovative skin has to block a considerable amount of sun radiation in summer, while it has to prevent heating energy from getting lost in winter. At the same time the skin has to allow for a high amount of (controlled) natural lighting and (controlled) natural ventilation. On the other side the iconic character of “signature” architecture pushes for glass façades to become almost dematerialized, a development further reinforced by recent advances in modern glass technology. Contemporary façades have to reach high transparency rates and have to follow extremely complex geometries - while still fulfilling requirements with regard to energy consumption and user comfort. The arising challenges for the façade engineer are therefore immense. The present paper presents various examples of how these challenges can be tackled in an appropriate way that units functionality, sustainability, and aesthetics